Versification : a short introduction - McAuley, James Phillip, 1917-1976 (Michigan State University Press, 1966)
Versification: A Short Introduction is written by one of Australia's most distinguished poets. The book discusses poetic meter, and may be the only source you need. McAuley devotes a short chapter to versification based on accent, syllable count, free verse and ""classical"" meters, but the book as a whole focuses on metrical verse and its constant reference back to stress in normal speech - it suceeds in showing meterical verse as a natural outgrowth of what we do naturally. This dispels quickly any sense of the esoteric - poetry is of and for people in general not for a spe